Quantum discretization of Landau damping - Castillo-López, S.G.; Pérez-Rodríguez, F.; Makarov, N.M. (Физика низких температур, 2018)
We derive and analyze analytical expressions for the quantum electron current density and electromagnetic field
distribution inside a metallic nanoslab. Besides, we obtain general explicit expressions for the surface impedances
of both metal slab boundaries. We found that the phenomenon of Landau damping manifests itself in the frequency
dependence of the surface impedances as resonances associated with the discretization of the electromagnetic and
electron wave numbers inside the metal nanoslab. In particular, the quantum nonlocal resonances of the surface impedances are clearly discernible at slab thicknesses smaller than the electromagnetic skin depth. The predictions for
the surface impedances in the quantum regime turn out to be radically different from those of the quantum local approach, the semiclassical Boltzmann kinetic equation formalism and the classical Drude–Lorentz local model. The
analytical study completely agrees with the respective numerical calculations. Отримано та проаналізовано аналітичні вирази для квантової густини електронного струму, а також для розподілу
електромагнітного поля всередині металевої нанопластини.
Виведено загальні точні вирази для поверхневих імпедансів
обох границь металевої пластини. Показано, що явище беззіштовхувального поглинання Ландау виникає в частотній
залежності поверхневих імпедансів у вигляді резонансів,
пов'язаних з дискретизацією електромагнітних та електронних хвильових чисел всередині металевої нанопластини.
Встановлено, що квантові нелокальні резонанси поверхневих
імпедансів добре помітні при товщинах пластини, менших
глибини електромагнітного скін-шару. Передбачена поведінка поверхневих імпедансів в квантовому нелокальному
режимі радикальним чином відрізняється від такої, що
проявляється в квантовому локальному наближенні, в напівкласичному підході кінетичного рівняння Больцмана, а також в класичній локальній моделі Друде–Лоренца. Аналітичне дослідження повністю узгоджується з відповідними
числовими обчисленнями. Получены и проанализированы аналитические выражения
для квантовой плотности электронного тока, а также для
распределения электромагнитного поля внутри металлической нанопластины. Выведены общие точные выражения для
поверхностных импедансов обеих границ металлической
пластины. Показано, что явление бесстолкновительного поглощения Ландау возникает в частотной зависимости поверхностных импедансов в виде резонансов, связанных с
дискретизацией электромагнитных и электронных волновых
чисел внутри металлической нанопластины. Установлено,
что квантовые нелокальные резонансы поверхностных импедансов хорошо различимы при толщинах пластины, меньших
глубины электромагнитного скин-слоя. Предсказанное поведение поверхностных импедансов в квантовом нелокальном
режиме радикальным образом отличается от того, которое
проявляется в квантовом локальном приближении, в полуклассическом подходе кинетического уравнения Больцмана,
а также в классической локальной модели Друде–Лоренца.
Аналитическое исследование полностью согласуется с соответствующими численными рассчетами.